2017
DOI: 10.1177/0284185116682381
|View full text |Cite
|
Sign up to set email alerts
|

Microdose acquisition in adolescent leg length discrepancy using a low-dose biplane imaging system

Abstract: Background Children with leg length discrepancy often undergo repeat imaging. Therefore, every effort to reduce radiation dose is important. Using low dose preview images and noise reduction software rather than diagnostic images for length measurements might contribute to reducing dose. Purpose To compare leg length measurements performed on diagnostic images and low dose preview images both acquired using a low-dose bi-planar imaging system. Material and Methods Preview and diagnostic images from 22 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…By using a computer algorithm, the system can construct three-dimensional (3D) surface images from the simultaneous two-plane images 5,6 . The MDSS is designed to lower patient doses compared with conventional digital radiography (DR) X-ray imaging systems and a few studies have shown substantial clinical potential for dose savings compared to DR and computed radiography (CR) [7][8][9][10][11][12] . The MDSS X-ray imaging system is mainly used to obtain overview images in patients with scoliosis and to measure the length of lower extremities.…”
Section: Introductionmentioning
confidence: 99%
“…By using a computer algorithm, the system can construct three-dimensional (3D) surface images from the simultaneous two-plane images 5,6 . The MDSS is designed to lower patient doses compared with conventional digital radiography (DR) X-ray imaging systems and a few studies have shown substantial clinical potential for dose savings compared to DR and computed radiography (CR) [7][8][9][10][11][12] . The MDSS X-ray imaging system is mainly used to obtain overview images in patients with scoliosis and to measure the length of lower extremities.…”
Section: Introductionmentioning
confidence: 99%
“…One study on the reliability of clinical assessments [ 27 ] had low risk of bias using the QAREL- checklist ( Table 3 ). Six studies on the validity of imaging diagnostics [ 59 61 , 67 , 70 , 71 ] had a low risk of bias and low concerns regarding applicability for all domains using QUADAS-2 tool ( Table 2 ). Only one study on the reliability of imaging diagnostics [ 68 ] had low risk of bias using the QAREL- checklist ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were included that used the bi-planar imaging system EOS TM for the determination of LLD [ 57 , 59 , 63 ]. In one study [ 59 ], preview images [radiation dose = 2.99 Gray x square centimeter (mGy x cm 2 )] recorded by the system were compared with diagnostic images (radiation dose = 239.26 mGy x cm 2 ). Furthermore, reliability of the methods was determined ( S2 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Система EOS представляет собой рентгенологический аппарат, позволяющий осуществлять сьемку в двух взаимно перпендикулярных проекциях [62,63]. Был проведен ряд исследований для оценки точности измерений разновеликости нижних конечностей [64,65,66]. Ввиду высокой точности получаемых результатов эталонный метод оценки не использовался.…”
Section: бипланарная система визуализации Eosunclassified